The Influence of Knowledge, Attitude, and Action on Fire Disaster Preparedness in Palu City Health Center - Salmawati, Lusia; Marselina; Pertiwi (Journal of Health and Nutrition Research, 2022)
This study aims to determine the effect of knowledge, attitudes, and actions on fire disaster management at the Palu Health Center. The type of research used was observational with a cross-sectional study design. The population of this study was all workers at the Palu City Health Center, totaling 81 people. The sample was taken based on a total sampling of 81 people and collecting data using questionnaires and observation sheets. Data analysis was performed using univariate, bivariate, and multivariate analysis using chi-square and likelihood tests to determine the relationship between variables and logistic regression tests to determine the most influencing variables. The results showed that there was no relationship between knowledge (p=0.774) and attitude (p=546) with fire prevention preparedness at the Palu City Health Center, and there was a relationship between action (p=0.028) and fire prevention preparedness at the Palu City Health Center. The most influential variable was the action variable (p=0.021). We suggest that the Palu City Health Center increase knowledge related to fire safety, emergency situations (fire) preparedness, and actions in overcoming fires for its employees.